SIMULATION OF THE PROCESS OF FILLING POLYSTYRENE FOAM FOUNDRY MOLD WITH THE METAL - SAVYTSKYI, YURYI (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Modern approaches to prefabrication production consist in the maximum approximation of the shape and size of the blanks to the finished part, which essentially makes the final part cheaper. One of the methods of precision casting is casting in gasified models, or foam models. The basis is the task of developing a theoretical model of filling a polystyrene foam model with liquid metal. The analysis of the process of filling the mold with a gasified model and the process of filling the mold with a closed sprue system are considered.The analysis of the obtained solutions shows that the movement of the metal has the character of aperiodic oscillations. The speed of metal in quantity is maximum at the initial moment of metal processing in the form and happens as it is filled. The pressure of the steam-gas mixture at the initial moment of time exceeds the pressure of the weak metal in the riser, which provides the possibility of metal ejection from the bowl. At the same time, the pressure in the mold cavity changes little with the increase in gas permeability of the mold, which is explained by the small gap between the melting front of the model and the metal mirror. However, with an increase in gas permeability due to a decrease in back pressure, the speed of the metal in the mold cavity and the path traveled by it increase. The analysis of the system of equations allows predicting the behavior of metal during the design of molds for the summer, which reduces the probability of production defects.
Keywords: casting; gasified models; polystyrene; gas; foundry form; castings